The Slovak language as a source for the reconstruction of the Proto-Slavic accentual system - Habijanec, Siniša (Baltistica, 2016)
Slovak is not generally thought of as a rich and informative source for the reconstruction of the Proto-Slavic accentual system. In addition to the well-known fact that Slovak, unlike Czech, exhibits no traces of the Proto-Slavic acute, this view is also due to at least two peculiarities of its development: 1. quantity is often neutralised by many later phonological processes, such as the Rhythmic Law and the shortening of front diphthongs after j; 2. Slovak is more prone to analogical levelling and generalisation than any other West Slavic language, affecting, among other things, the development of quantity, whether through the generalisation of length in a particular grammatical category (such as in the genitive plural) or through analogical intrusion of quantitative patterns in derivation. Nevertheless, Slovak does offer some valuable data for the reconstruction of the Proto-Slavic accentual system, such as consistent length in the nominative singular of short root vowel nouns belonging to the b accentual paradigm (bôb, kôl, stôl...). Still more valuable data is contained in the rich Slovak dialectal material, which is neither sufficiently well-known nor sufficiently accessible to international scholarship. This paper offers guidelines for researching quantity in the Slovak dialectal material, as well as shows how the Slovak dialectal material can contribute to the reconstruction of the Proto-Slavic accentual system.